Highlighting the Role of Acalypha indica Linn. Extract on Heart Rates with Myasthenia Gravis Rat Model - Desak Gede Budi Krisnamurti; Rani Wardani Hakim; Radiana Dhewayani Antarianto; Siti Farida; Erni Hernawati Purwaningsih; Jan Sudir Purba (Challenges and Advances in Pharmaceutical Research Vol. 4, 2022)
The present study determine the effect of extract of roots AI against the AChR and enzyme acetylcholinesterase in animal models NMJ-MG (Sprague-Dawley rats were injected with rocuronium bromide) on the autonomic nervous system on heart muscle, in this case, is heart rate (HR). Myasthenia gravis (MG) is a neuromuscular junction (NMJ) autoimmune disease caused by antibodies that attack components of the postsynaptic membrane, impairing neuromuscular transmission and causing skeletal muscle weakness and tiredness. The autonomic nervous system uses acetylcholine as a neurotransmitter. Immune attack on striated cardiac muscle can result in heart failure, arrhythmia, and abrupt death. Involvement of the heart rate (HR) has been claimed and reported, but a causal connection between MG and altered cardiac function has not been found. For this study of experimental autoimmune MG (EAMG) is used rocuronium, prostigmine, and Acalypha indica (AI) Linn. compared with HR. From the results, the study found that sympathetic activity of HR variability in EAMG injected with rocuronium 10 mg/kg body weight (BW). in 10 min significantly found increasing in measures of short-term variations in HR variability, indicating parasympathetic impairment. We conclude that in MG, cholinergic transmission is affected more diffusely than previously thought. Furthermore, AI was given orally. 30 mg/kg BW has an effect similar to the injecting of prostigmine 10 mg/kg BW that can reduce HR. Driven by the fact that the pharmacological treatment of MG is unsatisfied, it needs the therapeutic development for MG using herbal ingredients of AI. The result indicate the need for routine evaluation of autonomic functions in patients with MG both to identify patients at high risk for earlier consideration of cardioprotection and long-term follow- up studies. Furthermore, on the basis of these results using drugs rocuronium, prostigmine, and AI are associated with HR on EAMG, AI has the same effect with prostigmine. To know and learn more advanced study required.